The openness of open innovation in ecosystems: Integrating innovation and management literature on knowledge linkages - Christina Öberg; Allen Alexander (Journal of Innovation & Knowledge (JIK), 2019)
Open innovation has rendered increased interest both in practice and research, and has expanded from dyadic transfers of ideas, to ecosystem levels. Knowledge is at the heart of open innovation, and this paper describes and discusses knowledge-transfer linkages for open innovation. It does so based on a literature review. The paper links together open innovation research with general management research to categorise and discuss linkages among parties in terms of their openness and how they relate to knowledge management. Conclusions indicate that openness needs to be considered in different dimensions that also links to different knowledge management outcomes. The paper's contribution consists of how it connects open innovation research to the general management literature, and how it builds a practical understanding of how linkages between firms can be categorised to aid firms to consider which mechanisms they may choose and why.
Keywords: O32; 650; Company-to-company; Knowledge transfer; Linkages; Network; Open innovation; Relationship